New pharmacological effect of fulvestrant to prevent oxaliplatin‐induced neurodegeneration and mechanical allodynia in rats. Issue 8 (19th December 2018) - Yamamoto, Shota; Yamashita, Tomohiro; Ito, Mayu; Caaveiro, Jose M.M.; Egashira, Nobuaki; Tozaki‐Saitoh, Hidetoshi; Tsuda, Makoto
Abstract : Oxaliplatin, which is widely used as chemotherapy for certain solid cancers, frequently causes peripheral neuropathy. Commonly described neuropathic symptoms include aberrant sensations such as mechanical allodynia (hypersensitivity to normally innocuous stimuli). Although oxaliplatin neuropathy is a dose‐limiting toxicity, there are no established preventive strategies available at present. By screening several sets of small‐molecule chemical libraries (more than 3, 000 compounds in total) using a newly established in vitro high‐throughput phenotypic assay, we identified fulvestrant, a clinically approved drug for the treatment of breast cancer in postmenopausal women, as having a protective effect on oxaliplatin‐induced neuronal damage. Furthermore, histological and behavioural analyses using a rat model of oxaliplatin neuropathy demonstrated the in vivo efficacy of fulvestrant to prevent oxaliplatin‐induced axonal degeneration of the sciatic nerve and mechanical allodynia. Furthermore, fulvestrant did not interfere with oxaliplatin‐induced cytotoxicity against cancer cells. Thus, our findings reveal a previously unrecognised pharmacological effect of fulvestrant to prevent oxaliplatin‐induced painful peripheral neuropathy without impairing its cytotoxicity against cancer cells and may represent a novel prophylactic option for patients receiving oxaliplatin chemotherapy. Abstract : What's new? The anti‐cancer drug oxaliplatin frequently causes severe peripheral neuropathy. Although oxaliplatin neuropathy is a dose‐limiting toxicity, there are no established preventive strategies currently available. Using several sets of small‐molecule chemical libraries (more than 3, 000 compounds in total), here the authors identified fulvestrant, a clinically approved drug for breast cancer, as having a previously unrecognised preventive effect against oxaliplatin‐induced peripheral neuropathy. Fulvestrant thus attenuated oxaliplatin‐induced neurodegeneration in both in vitro and in vivo models. Importantly, fulvestrant did not impede oxaliplatin‐induced cytotoxicity against cancer cells, raising the possibility that fulvestrant may be useful as a novel prophylactic drug against oxaliplatin‐induced peripheral neuropathy.